Effective Community Participation in Planning and Operational Decision-Making in Iskandar Malaysia: A Qualitative In-Depth Interview Study - Khalid, Zanudin; Ibrahim, Ngah; Siti Hajar, Misnan; Zafikha Aida, Bidin (2022)
This study aimed to evaluate the effectiveness of community participation in planning and operational decision-making in Iskandar Malaysia. Iskandar Malaysia region consists of four local planning authorities responsible for planning and managing the spatial development in the region. Conceptually, effective community participation helps the local planning authority make a better decision, hence providing a sustainable and quality living environment. Therefore, the question raised is, “To what extent does the current community participation process offers a genuine opportunity to the community to incorporate their interest in the planning and operational decisions? The study employed in-depth interviews to gather insight of the phenomenon from various key actors to address the question. Following the 43 interviews performed, it is suggested that the effectiveness of community participation; and the incorporation of community interest in Iskandar Malaysia are substantially influenced by the functional variables like a collaboration between stakeholders, community's access to information and process; and intergovernmental relationship in planning. Structural and cultural variables include the skill and professionalism of public planners, capability to influence, public awareness and knowledge, and community's representation.